2015
DOI: 10.1002/chem.201501075
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into the Post‐Cyclization Isomerization in Gold‐Catalyzed 7‐exodig‐Hydroarylations

Abstract: The subsequent double-bond isomerization in the synthesis of dibenzocycloheptenes and their heteroaromatic analogues was investigated. In the case of biphenyls, a basic additive completely prevented an isomerization to the thermodynamic product. With electron-rich intramolecular heteroaromatic nucleophiles, the isomerization was still observed, but the kinetic product can be obtained by careful control of the reaction times in most cases. Mechanistic studies demonstrated that a slow isomerization is also possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Without acidic additive a mixture of 40 and the compound bearing an exo-methylene group was obtained. 22 AgNTf 2 and HNTf 2 alone were not catalytically active in this reaction. The total synthesis was completed after two steps furnishing Reticuol in 42% yield over 6 steps (Scheme 6b).…”
Section: Hydroarylation Of Alkynesmentioning
confidence: 81%
“…Without acidic additive a mixture of 40 and the compound bearing an exo-methylene group was obtained. 22 AgNTf 2 and HNTf 2 alone were not catalytically active in this reaction. The total synthesis was completed after two steps furnishing Reticuol in 42% yield over 6 steps (Scheme 6b).…”
Section: Hydroarylation Of Alkynesmentioning
confidence: 81%
“…This result suggested that the second arylation was accelerated by the additional methoxy group located at the para -position to the reacting carbon. 26 We then examined the kinetic isotope effect (eqn (4) in Scheme 6 ). The competition reaction using N -Boc-pyrroles 9F (2.5 equiv.)…”
Section: Resultsmentioning
confidence: 99%
“…Hashmi and his co-workers proposed the synthetic pathway of dibenzocycloheptane derivatives via gold-catalyzed post-cyclization isomerization (Scheme 10). 25 The 7- exo-dig hydroarylation reaction occurred with compound 20 and 5 mol% [L 6 Au(NTf 2 )] catalyst, 5 mol% of 2,6-di- tert -butylpyridine in deuterated benzene at 80 °C for 0.5–72 h and formed the desired product 21 in 41–95% yields. Compound 20 contained a di-substituted methoxyphenyl ring and gave a good yield of 95% after 3 h. When tert -butyloxycarbonyl (Boc)-protected pyrrole or indole ring was used, the tetracyclic molecule 21 was synthesized in moderate and high amounts, respectively (71% and 98%).…”
Section: Intramolecular Hydroarylation Reactionmentioning
confidence: 99%